A bestiary of monsters in Greek mythology - Syropulos, Spyridōn (Archaeopress Publishing Ltd, 2018)
This work explores the realm of the imaginary world of Greek mythology and presents the reader with a categorisation of monstrosity, referring to some of the most noted examples in each category